Transesterification of Lactic Acid Oligomers with Ethanol, a Way to Anhydrous Ethyl Lactate: A Kinetic Study - Figalla, Silvestr; Petrůj, Jaroslav; Švestková, Tereza (Molecules, 2018)
A new method for the preparation of anhydrous ethyl ester of lactic acid was studied. The selected method is based on catalytic transesterification of lactic acid oligomers, which were prepared for this purpose by autocatalytic oligomerization of lactic acid. In this work, a kinetic model for the case of catalytic alcoholysis of oligoesters was derived assuming a first-order reaction and equimolar content of reactants in the reaction mixture. The model makes it possible to obtain the values of the reaction rate and equilibrium constants and the equilibrium alcohol concentration by regression analysis at one time. The model was verified by measuring the rate of consumption of ethanol over the time at various reaction temperatures with anhydrous FeCl₃ as the catalyst. The reaction was studied at overpressure under autogenous conditions in the temperature range of 100⁻180 °C. For the catalyst concentration of 1 mol %, the activation energy value was 64.35 kJ·mol-1. The dependence of equilibrium composition and rate constant on the temperature was obtained. The derived model is generally applicable to all first-order equilibrium reactions. The presumption is that the forward and reverse reactions are of the same order and have the same stoichiometry and equivalent amounts of reactants at the beginning of the reaction.
Keywords: Catalysis; Kinetics; teplota; ethanol; katalýza; Lactic Acid; kyselina mléčná; Molecular Structure; tlak; Esterification; Lactates; esterifikace; Ethanol; Temperature; molekulární struktura; laktáty; Thermodynamics; termodynamika; kinetika; Pressure